Vol 2 No 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: PENGELOLAAN BUMDESA DALAM PRESPEKTIF EKONOMI SYARIAH (STUDI PADA BUMDES BANGUN KARYA DESA BANGUNREJO KECAMATAN PATEBON KAB. KENDAL) - Masruri, Masruri (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
Village Autonomy is a regional autonomy policy given to village governments to further optimize their potential so as to maximize village income for development and community welfare. Law Number 6 of 2014 concerning Villages explains that Village Government is the administration of government affairs and the interests of local communities in the government system of the Unitary State of the Republic of Indonesia. In improving the economy of the community, the Village Government establishing BUMDesa is the right step for the realization of the welfare of the village community. BUMDes are economic institutions established based on deliberations between the Village Government and the Village community based on the needs and potential of the Village. The management of BUMDesa is carried out by the village community. The role of a good Village Government in the management of BUMDesa will determine the success of BUMDesa. The type of research used in this study is descriptive qualitative. The data sources used in this study are primary data and secondary data. The sample in this study amounted to 8 people from a population of 964 households with a sampling technique, namely Nonprobability Sample by means of sample determination, namely purposive sampling. The data collection methods used by researchers consist of observation methods, interview methods and documentation methods. The data analysis technique goes through three stages, namely the data education stage, the data presentation stage (data display) and the data verification stage. The results showed that the Village Government in the management of BUMDesa Bangun Karya plays quite a role in terms of establishing and planning business units but in terms of advisory and supervision of BUMDesa performance, the Bangunejo Village Government has not played a full role in the management of BUMDesa Bangun Karya. The role of BUMDesa Bangun Karya in improving community welfare is the fulfillment of daily needs / types of trading businesses. Based on the principles of leaders in Islam, the Bangunrejo Village Government has not fully implemented the principles of leaders, due to the lack of transparency in the management of BUMDesa. The role of BUMDesa in improving community welfare according to the perspective of Sharia economics has played a perceived role in terms of meeting the needs of al-hajiyat and al-tahsiniyyat . However, to meet the needs of ad-dharuriyyat BUMDesa Bangun Karya has not played a role in improving the welfare of the community.